Food waste in Indonesia: Assessing readiness for valorization - Immawan, Taufiq (OPSI, 2024)
In Indonesia, 23-48 million tons of food waste are generated annually, causing economic losses of IDR 213-551 trillion or around 4-5% of GDP. Food waste offers potential for valorization into products like animal feed, organic fertilizer, and biofuel but faces challenges such as technological limitations, high costs, and safety concerns. This study examines the safety of food waste-derived products for human and animal use, focusing on applications in animal feed, the food industry, cosmetics, bio-refinery, and organic fertilizers. Key processes include contaminant removal and safety assessments, though limited studies address physicochemical, microbiological, and toxic contaminant evaluations. Identified gaps in Indonesian regulations, particularly regarding safety standards, highlight the need for clearer guidelines and support for eco-friendly technologies. Enhancing these frameworks can ensure the safe and sustainable valorization of food waste.